Rotavirus strain surveillance for three years following the introduction of rotavirus vaccine into Belém, Brazil. Issue 8 (16th April 2015) - Guerra, Sylvia F.S.; Linhares, Alexandre C.; Mascarenhas, Joana D'Arc P.; Oliveira, Alessilva; Justino, Maria Cleonice A.; Soares, Luana S.; Müller, Elza Caroline; Brasil, Patrícia; Tuboi, Suely; Ortega‐Barria, Eduardo; Colindres, Rómulo
<x xml:space="preserve">Abstract</x> The monovalent human rotavirus (RV) vaccine, RIX4414 (Rotarix™, GlaxoSmithKline Biologicals) was introduced into Brazil's Expanded Program on Immunization in March 2006. One year after vaccine introduction, the G2P[4] strain was found to be predominant, with an apparent extinction of many non‐G2 strains. This study investigated the diversity of circulating strains in the three years following RIX4414 introduction. Between May 2008 and May 2011, stool samples were collected from children aged ≥12 weeks who were hospitalized for severe lab confirmed RV‐gastroenteritis (≥3 liquid or semi‐liquid motions over a 24‐h period for <14 days, requiring ≥1 overnight hospital stay and intravenous rehydration therapy) in Belém, Brazil. RV‐gastroenteritis was detected by ELISA and the G‐ and P‐types were determined by RT‐PCR assays. During the first year of surveillance nucleotide sequencing was used for typing those samples not previously typed by RT‐PCR. A total of 1, 726 of 10, 030 severe gastroentertis hospitalizations (17.2%) were due to severe RVGE. G2P[4] was detected in 57.2% of circulating strains over the whole study period, however it predominated during the first 20 months from May 2008 to January 2009. G1P[8] increased in the last part of the study period from May 2010 to May 2011 and represented 36.6% (112/306) of the circulating strains. G2P[4] was the predominant RV strain circulating during the first 20 months of the study, followed by G1P[8]. These findings probably reflect a natural fluctuation in RV strains over time, rather than a vaccine‐induced selective pressure. J. Med. Virol. 87:1303–1310, 2015. © 2015 Wiley Periodicals, Inc.